2019
DOI: 10.3389/fmicb.2019.01748
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Riboflavin Production by Lactobacillus plantarum Strains and Tracking of Their Gastrointestinal Survival and Functionality in vitro and in vivo Using mCherry Labeling

Abstract: Some strains of lactic acid bacteria (LAB) produce riboflavin, a water-soluble vitamin of the B complex, essential for human beings. Here, we have evaluated riboflavin (B2 vitamin) production by five Lactobacillus plantarum strains isolated from chicha , a traditional maize-based fermented alcoholic beverage from north-western Argentina and their isogenic riboflavin-overproducing derivatives previously selected using roseoflavin. A direct fluorescence spectroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 38 publications
7
46
2
Order By: Relevance
“…This bacterial suspension was further used for the fermentation experiments. Subsequently, 5 mL of the heated soymilk was inoculated with 4% (v/v) of the bacterial suspension and then fermented at different temperatures (23,30,37,44, and 50 • C) and for different times (4,8,12,16,20, and 24 h). For each fermentation experiment, 5 mL of heated aseptic soymilk without bacterial inoculation was used as a control.…”
Section: Preparation Of Soymilk and Soymilk Fermentationmentioning
confidence: 99%
See 2 more Smart Citations
“…This bacterial suspension was further used for the fermentation experiments. Subsequently, 5 mL of the heated soymilk was inoculated with 4% (v/v) of the bacterial suspension and then fermented at different temperatures (23,30,37,44, and 50 • C) and for different times (4,8,12,16,20, and 24 h). For each fermentation experiment, 5 mL of heated aseptic soymilk without bacterial inoculation was used as a control.…”
Section: Preparation Of Soymilk and Soymilk Fermentationmentioning
confidence: 99%
“…The wild-type RYG-YYG-9049 and its M10 strains were applied to ferment soymilk to increase its riboflavin content. The effects of main fermentation parameters, including temperature (23,30,37,44, and 50 • C) and time (4,8,12,16,20, and 24 h) were investigated on riboflavin production. A decrease in the pH of the fermented soymilk was observed during the fermentation process ( Figure 5A), but this decrease was very slight at a fermentation temperature of 50 • C because of no accumulation of lactic acid, indicating that the strain could not grow or even died at 50 • C. Therefore, riboflavin in soymilk fermented at 50 • C was detected.…”
Section: Ryg-yyg-9049 and Its M10 Fermentation Increased Riboflavin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…To follow the growth and fluorescence of L. plantarum strains in real time, the method described by Mohedano et al (2019) was used. Simultaneous spectrophotometric monitoring of growth at 37 • C and of the fluorescence of the bacterial cultures was performed using the Varioskan Flask System (Thermo Fisher Scientific, USA) and sterile 96-well optical white w/lid cell culture polystyrene plates (Thermo Fisher Scientific, USA).…”
Section: Simultaneous Detection Of Bacteria Growth and Riboflavin Or mentioning
confidence: 99%
“…These vitamin B2-overproducing LAB have also been used to standardize fluorescent detection of riboflavin production in real time during growth (Mohedano et al, 2019) and also showed the potential of strains L. plantarum M5MA1-B2 and M9MG6-B2, as producing high levels of riboflavin and possessing good technological properties. Both strains carry a different punctual mutation in the same position (G19A and G19C in the M5MA1-B2 and M9MG6-B2 strains, respectively) located in the regulatory region of the rib operon (Mohedano et al, 2019). Furthermore, the comparative analysis of the genomes of five of the parental riboflavin producing strains, as well as assessing some criteria to determine their food safety, revealed a great similarity between the strains studied.…”
Section: Introductionmentioning
confidence: 99%